Discretion and management of the covid-19 pandemic: Indonesia’s experience in facing the health crisis - Muhammad Doing; Bujang Ali; Dedi Yamin (Institute Of computer Science (IOCS), 2024)
With this study, we want to better understand the role of discretion in the Indonesian government's response to the COVID-19 outbreak, so that we may develop a more equitable and effective policy framework while reducing unintended consequences for as many people as possible. To understand and evaluate legislative regulations and government decisions, especially in the context of social restriction policies and their impact on individual basic rights, this study employs a normative juridical approach, which necessitates analysis of primary, secondary, and tertiary legal materials and the use of legal hermeneutics. According to the findings, Indonesia's legal framework explicitly provides for the use of discretion when dealing with COVID-19, allowing the government and state authorities to respond swiftly and properly to changing circumstances. The key to preventing abuse of authority and prejudice is ensuring openness, accountability, and human rights values in the exercise of discretion. To make sure discretion is both responsive and respectful of democratic norms and human rights, we suggest regulatory changes and strengthened human rights-based supervision procedures.